2004
DOI: 10.1007/s00264-004-0590-x
|View full text |Cite
|
Sign up to set email alerts
|

Femoral shaft medialisation and neck-shaft angle in unstable pertrochanteric femoral fractures

Abstract: We analysed the time-dependent mean changes in the femoral neck length, neck-shaft angle and hip offset in a randomised study comprising 48 patients who were treated with the dynamic hip screw (DHS) or the proximal femoral nail (PFN) for an unstable intertrochanteric femoral fracture. As a consequence of fracture compression, the mean post-operative neck length was significantly shorter in patients treated with the DHS. During the first 6 weeks after the operation, a mean decrease of 4.6°w as observed in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 20 publications
4
47
2
5
Order By: Relevance
“…Unstable A2 fractures should be initially reduced to a slightly valgus position during PFN surgery, because the neck-shaft angle would decrease during the first 6 postoperative weeks. 19 The lag screw should be inserted into the femoral head as deeply as noted in the AP view, and centrally in the lateral view. 13 The tip of the lag screw should always be inferior to the centre of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…Unstable A2 fractures should be initially reduced to a slightly valgus position during PFN surgery, because the neck-shaft angle would decrease during the first 6 postoperative weeks. 19 The lag screw should be inserted into the femoral head as deeply as noted in the AP view, and centrally in the lateral view. 13 The tip of the lag screw should always be inferior to the centre of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…So the choice of the implant is particularly critical in unstable fractures. This is reflected in the clinical situation where the failure rate in unstable fractures is significantly increased compared to stable fractures [1,21,29]. Although these complications in unstable fractures are largely related to the local mechanical situation at the fracture site, no standardized biomechanical model exists to study the mechanical characteristics of hip fracture osteosynthesis [12].…”
Section: Introductionmentioning
confidence: 99%
“…The most important finding of their series was that the mean NSA angle decreased in both treatment groups. This decrease was more distinct in the DHS group, but the difference in patients treated with the PFN was not significant [3] . In another study conducted by Barwar N et al showed that there is a high incidence of coxa vara or coxa valga in fixation with standard dynamic hip screw and restoration of NSA could often not be achieved.…”
Section: Discussionmentioning
confidence: 85%